2008
DOI: 10.1530/rep-07-0480
|View full text |Cite
|
Sign up to set email alerts
|

The absence of corpus luteum formation alters the endocrine profile and affects follicular development during the first follicular wave in cattle

Abstract: We previously established a bovine experimental model showing that the corpus luteum (CL) does not appear following aspiration of the preovulatory follicle before the onset of LH surge. Using this model, the present study aimed to determine the profile of follicular development and the endocrinological environment in the absence of CL with variable nadir circulating progesterone (P 4 ) concentrations during the oestrous cycle in cattle. Luteolysis was induced in heifers and cows and they were assigned either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…In contrast, CL-absent cows (low P 4 concentration) have been shown to have a higher E 2 concentration than CL-present cows (high P 4 concentration). which in turn leads to a higher LH pulse frequency that enhances the follicular growth (21). Nevertheless, it should be emphasized that, for cows diagnosed as non-cycling, the major underlying factor for compromised follicular development could be the low LH pulse frequency, although, other metabolic hormones like IGF-1, insulin, growth hormone (GH) that are involved and crucial for normal follicular development should not be avoided (3).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CL-absent cows (low P 4 concentration) have been shown to have a higher E 2 concentration than CL-present cows (high P 4 concentration). which in turn leads to a higher LH pulse frequency that enhances the follicular growth (21). Nevertheless, it should be emphasized that, for cows diagnosed as non-cycling, the major underlying factor for compromised follicular development could be the low LH pulse frequency, although, other metabolic hormones like IGF-1, insulin, growth hormone (GH) that are involved and crucial for normal follicular development should not be avoided (3).…”
Section: Discussionmentioning
confidence: 99%
“…When the ovulatory follicle arises in a follicular wave that develops in the absence of P4 (i.e., no active CL), codominant follicles resulting in double ovulations occur more frequently (Wiltbank et al, 2000;Hayashi et al, 2008). This is particularly the case for anovular cows at first postpartum ovulation, which had a 41% doubleovulation rate, compared with 4% for cycling cows (GĂŒmen et al, 2003).…”
Section: Progesterone After Timed Aimentioning
confidence: 99%
“…For example, cattle that grow the ovulatory follicular wave in the absence of P4 have an increased percentage of cows with co-dominant follicles and double ovulation (Hayashi et al, 2008). Manipulative studies have now been performed that have demonstrated a decrease in the percentage of cows that double ovulate when circulating P4 is increased (Stevenson et al, 2007a;Cunha et al, 2008;Cerri et al, 2011a).…”
Section: Cellular Mechanisms Regulating P4 Actionmentioning
confidence: 99%